A narrative analysis positioning HIV relative to personal (sexual) relationship challenges in an agony aunt column in the Western Cape, South Africa – Aunty Mona's "love advice". (2nd June 2016) - Viljoen, Lario; Thorne, Marguerite; Thomas, Angelique; Bond, Virginia; Hoddinott, Graeme; ,
ABSTRACT: HIV prevalence and incidence in South Africa remain high, making HIV a part of everyday life. Community narratives on HIV treatment and prevention are important and influence official and unofficial health messaging and community perceptions and understandings of HIV. We explore how contributors and the columnist of an agony aunt column position HIV relative to choices made about love, partnership, and sex over three years. We analysed all columns of an agony aunt series ( Antie Mona ) published between December 2012 and November 2015. The column is published in a South African, Afrikaans-language newspaper " Son ", prioritising sensationalist news items. Trends were identified through narrative analysis. Data were managed in ATLAS.ti and inductive, iterative coding conducted. It was found that letters to the agony aunt rarely refer to HIV directly (less than 7%). Euphemisms such as diseases of the flesh and the great flu were more commonly used instead of HIV or AIDS. Letters addressed HIV in three ways: direct references to experiences living with HIV; direct questions about HIV prevention; and scenarios where HIV could (from a public health perspective) have been the main concern, but everyday issues took precedence. The majority of letters fell into this latter category where the writers focused on the immediate concerns of good sexual relations, problems related to love and romantic relationships, good moral behaviour of others, and issues of oppressive life conditions rather than on HIV directly. The findings illustrate that informal, public contributions to health information, such as agony aunts, are important narratives that inform popular perspectives on HIV and health. A better appreciation of this context would allow health implementers to ensure that these role players receive updated health messaging to avoid the risk of HIV-related stigma where HIV is used as a moral rod to punish perceived moral transgressions.